Effects of lactic acid bacteria and coagulase-negative staphylococci on dry-fermented sausage quality and safety: Systematic review and meta-analysis - Stegmayer, María Ángeles; Sirini, Noelí Estefanía; Ruiz, María Julia; Soto, Lorena Paola; Zbrun, María Virginia; Lorenzo, José Manuel; Signorini Porchiett, Marcelo Lisandro; Frizzo, Laureano Sebastián (Elsevier, 2024)
The meta-analysis aim was to confirm and quantifying the influence of starter cultures on microbiological and physical-chemical parameters of dry-fermented sausages at the end fermentation stage. The literature search yielded 1194 citations, and 77 studies with 178 experiments were eligible and included in the meta-analysis, a random-effects model was used to estimate the pooled weighted mean difference (MD) with 95% confidence interval (CI).The use of starter culture in dry-fermented sausages significantly reduced pH (MD: -0.364; CI: −0.414; −0.319), moisture (MD: -1.443; CI: −1.931; −0.955), aw (MD: -0.011; CI: −0.017; −0.006), Enterobacteriaceae count (MD: -1.119; CI: −1.293; −0.945), yeasts and molds count (MD: -0.351; CI: −0.691; −0.084), and increased color component a* (MD: 0.859; CI: 0.266;1.452), color component L* (MD: 1.288; CI: 0.433; 2.143), LAB count (MD: 0.981; CI: 0.696;1.267), Staphylococci count (MD: 0.484; CI: 0.293; 0.675) and TVC (MD: 0.529; CI: 0.098; 0.959). The results of the sub-analysis suggest that the addition of LAB and LAB/CNS inocula have a greater effect on the physico-chemical and microbiological parameters studied in this work. In the meta-regression analysis, a positive linear relationship was found in starter culture sausages in comparison with control batch between LAB count and the dose of starter culture added, and in the pH and Enterobacteriaceae count with the passage of fermentation days. In contrast, a negative linear relationship was found between redness and increased casing diameter of the sausages. Therefore, our work shows impact that addition of starter cultures has on safety and quality of dry-fermented sausages.